Charge Carrier Dynamics and Bandgap Modulation in Doped ZnWO4 Nanocomposites - Abubakar Ladio, Hassan; Abubakar, A. A; Nasir Z. J. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
This study investigates the effects of doping on the bandgap energy of synthesized and doped ZnWO4 nanomaterials. The synthesized nanomaterials were doped with varying concentrations (1%, 3%, 5% & 7%) of the nonmetals nitrogen, carbon and boron. The optical, morphological and textural nature of the prepared nanomaterials were characterized by different analytical tools. The UV-Visible/HRTEM/XRD analysis confirmed that the incorporation of the dopants which had an impact on the band gap energy but did not significantly alter the host material’s phase or produce defects, the orientation and growth pattern of the doped ZnWO4 along [021] plane was observed. There was an observed decrease in the bandgap energy upon doping from 4.68 eV to 2.31 eV, 2.0 eV and 2.30 eV for 7%N-ZnWO4, 7%C-ZnWO4 and 7%B-ZnWO4. There was also an increase in the relative crystallinity of the nanocomposite materials. The XRD results obtained showed a decrease in crystallite size of most of the nanomaterials with the lowest for each dopant being 8.11 nm, 7.64 nm, 7.25 nm for 1%N, 3%C and 3%B respectively, the XRD results also corroborated with the HRTEM results obtained. The results from the characterization revealed that doping was successful at improving the efficiency of the synthesized ZnWO4 nanoparticles.